Exploring temple floral refuse for biochar production as a closed loop perspective for environmental management. (July 2018) - Singh, Pardeep; Singh, Rishikesh; Borthakur, Anwesha; Madhav, Sughosh; Singh, Vipin Kumar; Tiwary, Dhanesh; Srivastava, Vimal Chandra; Mishra, P.K.
Graphical abstract: Highlights: Socio-environmental issue of temple floral refuse management studied. Preparation of biochar from temple floral refuse is explored. Characterization of floral refuse biochar is performed using various techniques. Floral refuse biochar showed strong adsorptive behaviour for methylene blue dye. A closed loop (refuse-dye-biochar-adsorbent-soil ameliorant) approach is presented. Abstract: Religious faith and ritual activities lead to significant floral offerings production and its disposal as waste to the nearby open lands and water bodies. These activities result into various social and environmental nuisances because of their high organic content. Alternatively, it can be used as valuable resources for various biochemical and thermo-chemical processes. Floral refuse has been utilized in natural dye extraction, however, the residual solid refuse is of significant environmental concern due to its nutrient rich nature. This study explores the potential utilization of solid residue of temple floral refuse after natural dye extraction by thermo-chemical decomposition of it. The slow pyrolysis of solid residue was performed at 350 °C and 500 °C, and the biochar yield of 42 and 36% was obtained, respectively. TGA-DTG analysis was performed to observe the thermo-chemical behaviour of floral refuse. The biochar products were further characterized by FTIR, SEM, EDX, BET, XRD, and RAMAN spectroscopy to observe the impact of pyrolysis temperature (PT) on the resulting material, i.e. biochar and its possible application measures. EDX results revealed the presence of various macro-nutrients such as C, N, P, K Ca and Mg in different proportions which showed its soil amelioration potential. Moreover, based on the SEM and BET results, biochar prepared at 500 °C was further explored for adsorption of methylene blue dye at various dose and pH conditions. Based on Langmuir (R 2 = 0.98) and Freundlich (R 2 = 0.97) isotherms, it is found as a potential adsorbent material for removal of methylene blue dye. The results revealed that biochar conversion of colour extracted floral refuse can be a vital option for quick and efficient management of it in a closed loop approach.